Acupuncture for carpal tunnel syndrome: A systematic review and meta-analysis of randomized controlled trials - Dong, Qinjian; Li, Xiaoyan; Yuan, Ping; Chen, Guo; Li, Jianfeng; Deng, Jun; Wu, Fan; Yang, Yongqiu; Fu, Hui; Jin, Rongjiang (Frontiers in Neuroscience, 2023)
Background: The evidence of acupuncture for patients with carpal tunnel syndrome (CTS) is insufficient. This systematic review and meta-analysis conducted comprehensive search and aimed to evaluate the effect of acupuncture for CTS. Method: English and Chinese databases were searched from their inceptions to October 27, 2022, to collect randomized controlled trials (RCTs) investigating the effect of acupuncture for CTS. Two independent reviewers selected eligible studies, extracted data, assessed the risk of bias using the revised Cochrane risk-of-bias tool for randomized trials (ROB 2) and appraised the reporting quality of intervention with the Revised Standards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA). The primary outcome was the symptom severity and functional status, and secondary outcomes included pain intensity, responder rate, and electrophysiological parameters. RevMan software (version 5.4.1) was used for data analysis. The certainty of evidence was rated with GRADEpro (version 3.6) software. Results: We included 16 RCTs with a total of 1,025 subjects. The overall risk of bias of 1 RCT was rated as low risk of bias, 14 were some concerns, and 1 was high. As a monotherapy, acupuncture was not superior to sham acupuncture in improving symptom severity. Compared with night splints, acupuncture alone was more effective to relief pain, but there were no differences in symptom severity and functional status. Acupuncture alone had no advantage over medicine in improving symptom severity and electrophysiological parameters. As adjunctive treatment, acupuncture might be benefit for CTS in symptom severity, functional status, pain intensity, and electrophysiological parameters, and was superior to medicine in improving the above outcomes. However, acupuncture as adjunctive therapy was not better than sham acupuncture in improving symptom severity and functional status. Few acupuncture-related adverse events were reported. The above evidence had low or very low certainty. Conclusion: Acupuncture as an aadjunctive treatment may be effective for patients with CTS. And more rigorous studies with objective outcomes are needed to compare acupuncture with sham acupuncture or with other active treatments.